(untitled) (Research, Society and Development, 2020)
The aim of this study was to develop and characterize creamy sweet from the pomace of vinified Vitis vinifera grapes. The pomace was selected and characterized by physical-chemical, microbiological and bioactive compounds analyzes. After processing, two creamy sweets were formulated, one with industrial pectin (Pectin) and other with agar gum and carrageenan (Gums). The creamy sweets were characterized by physical-chemical, microbiological, bioactive compounds, rheological and sensory tests. Mold and yeast count was higher (p<0.05) in pomace (3.5x102 UFC.g-1) than in the creamy sweets (<102 UFC.g-1). The content of moisture and acidity were lower (p<0.05) in creamy sweets (Gums: 34.75% and 0.48%; Pectin: 35.54% and 0.47%) than in pomace (69.38% and 0.77%) (respectively). The carbohydrate content and pH were higher (p <0.05) in creamy sweets (Gums: 50.39% and 3.56; Pectin: 48.05% and 3.53) than in pomace (10.73% and 3.24) (respectively). The formulations showed pseudoplastic behavior. Despite a significant reduction (p<0.05) in the anthocyanin values ​​of the pomace (13.1 mg.g-1) for Pectin (3.61 mg.g-1) and Gums (3.93 mg. g-1), pomace carotenoids (14.63 mg.g-1) for Pectin (1.89 mg.g-1) and Gums (3.60 mg.g-1), and total pomace phenols (13.32 mg.g-1) for Pectin (8.77 mg.g-1) and Gums (9.59 mg.g-1), there was no difference in antioxidant capacity (p>0.05). In the global assessment and in the preference test, Pectin obtained higher results (89.22% and 88%) than Gums (78.55% and 12%) (respectively). It was concluded, therefore, that the vinified grape pomace can be used for the production of creamy sweets.